EFEK HEPATOPROTEKTIF SERBUK AKAR PASAK BUMI (Eurycoma longifolia Jack.) DILIHAT DARI AKTIVITAS SGPTSGOT TIKUS JANTAN YANG DIINDUKSI CCl4 - Wirawan Adikusuma; Moch. Saiful Bachri (Universitas Ahmad Dahlan, 2014)
This study was designed to evaluate the hepatoprotective effect of the powder Eurycomalongifolia Jack. From the activity level of SGPT-SGOT on CCl4-induced in male rats. Twentyfive male rats (150-250 g) divide in to 5 groups. Group I treated with aquadest was kept asnormal, group II treated with a single dose of CCl4 (1 ml/ kg BW i.p), group III and IV weretreated with Eurycoma longifolia Jack. (100 mg/kg BW and 200 mg/kg BW p.o) respectivelyand CCl4 (1 ml/kg BW i.p), group V treated with a single dose of curcumin (100 mg/kg BWp.o) and CCl4 (1 ml/kg BW i.p). Blood was collected from vena porta for determination ofSGPT-SGOT. The study showed the activity level of SGPT from the rats was treated byEurycoma longifolia Jack. 100 mg/kg BW and 200 mg/kg BW, Curcumin, and control groupsare 150.0±5.099 U/L; 113.6±5.508 U/L; 60.5±2.887 U/L; and 129.0±6.055 U/L respectively. Mean while the activity level of SGOT from the rats was treated by Eurycoma longifolia Jack.100 mg/ kg BW and 200 mg/ kg BW, Curcumin, and control groups are 369.4±11.165;263.0±1.803; 194.5±7.448; and 451.5±16.759 U/L respectively. The Eurycoma longifoliaJack. powder and Curcumin significantly (p < 0.05) declines two enzymes (SGPT and SGOT)than control group. The results concluded that Eurycoma longifolia Jack. powder hashepatoprotective effect.